Multifunctional theranostic magnetic PLGA nanoparticles encapsulating cyclosporine A: addressing challenges in pancreas transplantation for type 1 diabetes - Rocha, Cátia Vieira; Magalhães, Andreia Patrícia; Diego-González, Lara; Gonçalves, Victor; Kotrulev, Martin; Gomez-Touriño, Iria; Bañobre-López, Manuel; Gallo, Juan (Frontiers in Immunology, 2026)
Type 1 Diabetes (T1D) is a high-incidence chronic autoimmune disease, with patients requiring lifelong insulin therapy. In the most severe cases, pancreas transplantation (PTA) arises as the first choice of treatment for these patients in the hope of achieving insulin independence. However, the long-term success of PTA is hindered by ischemia-reperfusion injury (IRI) and immune rejection, both of which limit graft survival. To address these challenges, we have developed multifunctional theranostic nanoparticles (t-PLGA NPs) co-encapsulating Fe3O4 and MnO NPs, along with cyclosporine A, an immunosuppressive drug. These immunomodulating NPs serve as dual contrast agent for MRI, while generating oxygen to combat hypoxia during IRI. The t-PLGA NPs exhibit efficient drug encapsulation and sustained release, enhancing immunosuppression while minimizing systemic toxicity. In vitro studies also demonstrated the NPs’ ability to suppress the immune system, validating the NPs’ potential to prevent graft rejection. The combination of imaging and therapeutic properties makes this platform highly promising for improving PTA outcomes in T1D patients.